Steady-State Thermal Modeling of Salient Pole Synchronous Generator - Payam Shams Ghahfarokhi; Andrejs Podgornovs; Ants Kallaste; Antonio J. Marques Cardoso; Anouar Belahcen; Toomas Vaimann; Oleg Kudrjavtsev; Bilal Asad; Muhammad Naveed Iqbal (Energies, 2022)
This paper presents a practical thermal model of a synchronous generator for high-power applications. This model couples the lumped parameter thermal network and coolant network together to utilize the impact of the coolant’s temperature rising over the machine. Furthermore, the advanced multi-planes technique provides a more precise and higher resolution temperature distribution of various machine sections. Therefore, the machines are divided into five planes; three belong to the active part, and two are added to model the machine’s drive and non-drive end-regions. Furthermore, the paper pays special attention to describing the challenges and providing solutions to them during the heat transfer modeling and analysis. Finally, the analytical model is verified using experimental results on a synchronous generator with a salient pole rotor and an open self-ventilation (OSV) cooling system by comparing the analytical and experimental results. As a result, good correspondence between the estimated and measurement results is achieved.